LIFESTYLE OF POLYCYSTIC OVARY PATIENTS IN TRESNA MATERNITY HOSPITAL, MATARAM CITY IN 2020 - Pramita Putri Utami; Nurul Hidayati; Ziadatul Munawarah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Not a few married couples have to wait a long time to have children, some have even given up on having a baby because they have been married for a long time, and the wife has not yet conceived. This situation is usually called infertility or in medical language is known as infertile. One of the factors that cause infertility comes from an unhealthy lifestyle. The number of infertile couples is one of them Polycystic Ovary (PCO) at Tresna Maternity Hospital based on information from existing data. PCO are small follicles measuring 5-7 mm or 0.5-0.7 cm. This study aims to determine the lifestyle of patients Polycystic Ovary at Tresna Maternity Hospital Mataram City in 2020. This research was included in a descriptive design study which was conducted on 6-20 September 2020 at Tresna Maternity Hospital, Mataram City. The population in this study were mothers who had Polycystic Ovary with a sample of 26 people with a sampling technique total sampling where the sampling technique uses the total population. Data analysis using univariate analysis. Research that has been conducted on 26 samples can be seen that most of the mothers suffer from it Polycystic Ovary 18 samples (69.2%) are aged 20-35 years and the majority of mothers who have a healthy lifestyle are 22 samples (84.6%). Conclusion, suffering mother Polycystic Ovary already live a healthy lifestyle, so it is hoped that mothers will pay more attention to their lifestyle such as exercise and food consumed so that their lifestyle will be better.